A Pre-Clinical Animal Study for Zonal Articular Cartilage Regeneration Using Stratified Implantation of Microcarrier Expanded Zonal Chondrocytes. (April 2022) - Tee, Ching Ann; Yang, Zheng; Wu, Yingnan; Ren, Xiafei; Baranski, Maciej; Lin, Daryl Jimian; Hassan, Afizah; Han, Jongyoon; Lee, Eng Hin
Objective: The zonal properties of articular cartilage critically contribute to the mechanical support and lubrication of the tissue. Current treatments for articular cartilage have yet to regenerate this zonal architecture, thus compromising the functional efficacy of the repaired tissue and leading to tissue degeneration in the long term. In this study, the efficacy of zonal cartilage regeneration through bilayered implantation of expanded autologous zonal chondrocytes was investigated in a porcine chondral defect model. Design: Autologous chondrocytes extracted from articular cartilage in the non-weight bearing trochlea region of the knee were subjected to an expansion-sorting strategy, integrating dynamic microcarrier (dMC) culture, and spiral microchannel size-based zonal chondrocyte separation. Zonal chondrocytes were then implanted as bilayered fibrin hydrogel construct in a porcine knee chondral defect model. Repair efficacy was compared with implantation with cell-free fibrin hydrogel and full thickness (FT) cartilage-derived heterogenous chondrocytes. Cartilage repair was evaluated 6 months after implantation. Results: Sufficient numbers of zonal chondrocytes for implantation were generated from the non-weight bearing cartilage. Six-month repair outcomes showed that bilayered implantation of dMC-expanded zonal chondrocytes resulted in substantial recapitulation of zonal architecture, including chondrocyte arrangement, specific Proteoglycan 4 distribution, and collagen alignment, that was accompanied by healthier underlying subchondral bone. Conclusion: These results demonstrate that with appropriate expansion and isolation of zonal chondrocytes, the strategy of stratified zonal chondrocyte implantation represents a significant advancement to Autologous Chondrocyte Implantation-based cartilage regeneration, with the potential to improve the long-term integrity of the regenerated tissues.